Confinamento topológico em grafeno sob regime de novas estruturas globais - Pinheiro, Hudson Pacheco (2014)
In this paper we review the theoretical basis of the topological confinement in bilayer graphene. This confinement is obtained by applying an electric potential between the layers of graphene and can control the width of the gap between the layers of conduction and valence Dirac defined by points K~ and K~ 0. These structures are characteristic of defects of a structure of domain walls interpolating regions with different polarities. In our specific case, we used a method that was recently introduced in the scientific literature and has already generated interesting results in high energy physics, especially in the brane scenario, called multikink model in one dimension. The defect structures produced by this method allowed the analysis of confinement for potential profile with a kink, kink-2, 3-and 4-kink kink. In this context, we show the appearance of chiral modes zero, that is topologically confined states in the bilayer graphene, as well as new low-power states in addition to the already known intragap states. We also show that the profile used is kink-kink or kink-antikink, modifies the curves representing the quiriais states in the structures of the energy levels.